RELACIJE MORFOLOŠKIH KARAKTERISTIKA I PLIVAČKO - SITUACIONIH SPOSOBNOSTI SELEKCIONISANIH VATERPOLISTA - Dimitrije Popovski; Marko Aleksandrović; Dejan Madić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
Modern sports theory and praxis points an importance of morphological characteristics for orientation and selection in many sport disciplines. In equation of specification of every sport and specific position in equip even, morphological characteristics are an important factor. Specific morphological characteristics of players are needed for technical and tactical quality achievement in water polo, because they determine biomechanical laws of movement and locomotion. Water polo game development demands of player complete preparation. Most of these demands are in field of morphological characteristics, so it should be take care in selection period. The goal of paper is to establish influence of morphological characteristics on situation- motorical abilities of water polo players in early selection period. 85 water polo players, aged 12-13, at least 2 years sport experience are investigated. 12-tests battery is used for morphological characteristics estimation, 6-tests battery for space situation-motorical and swim abilities. Results are processed by canonical correlation analysis. Results of this research will be significant in candidate selection for water polo and training process improvement.